A Research Review of Motivation-Enhancing of Human Resource Practices - Hadziahmetovic, Nereida; Dinc, M. Sait; Jahic, Kanita (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
This analysis of 115 articles about motivation-enhancing human resource practices articles published in seven Human Resource Management journals in a period between 2010 and 2015 presents significant contributions of individual scholars and institutions to research of motivation-enhancing human resource practices. Coauthor relationship is found through network analysis in order to show interrelationship among scholars who have contributed to this research. However, in order to provide main categories and subcategories in the field, authors carried out content analysis of the articles. Moreover, research locations, and methodologies of the articles are analyzed. Finally, to demonstrate recent trend of the research of motivation-enhancing human resource practices in the aforementioned period, this study provides some essential information such as number of articles published in each journal and in each year.